Soberanía en disputa. Abuso, prostitución y prácticas policiales en Puerto Inirida, 1965-1969 (2019)
The article analyzes the ambiguous relationship between police practices and sovereignty on the basis of the first cases and reports prepared by the police authorities of the Comisaria del Guainia (administrative division in the Colombian Amazon region), created in 1965. It specifically shows how police practices were part of the production of a new social order, in which appealing to State authority and the regulation of conflicts associated with prostitution shaped the forms of appearance of the State in Puerto Inirida between 1965 and 1969. More than controlling or monitoring social life there, the Police mediated and participated in transgressions that occurred in the political sphere (abuse of authority) and in that of morality (prostitution and everyday conflicts). Many of the violations of the public and police orders were committed by State officials, while, at the same time, police practices combined public functions and personal conflicts.